A Retrospective Study on the Prevalence of Iron Deficiency Anemia Frequency in Rural Areas of Disrict Faisalabad - Amin Anjum, Nida, Shabana Kiran, Tariq Mahmood Malik, Hamza Ashraf, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To evaluate the prevalence of different anemic grades in patients to give better treatment and to improve quality of life of patients. Material and Methods: This retrospective study was conducted to analyze the immensity of Deficiency of Iron Anemia in DHQ Hospital Faisalabad, and the duration of this study was from February 2021 to January 2022 to evaluate the prevalence and different stages of anemic patients. Two hundred patients were included in this study who met all the criteria needed to this study. In this study we examined blood tests, CBC reports of all patients in the laboratory. Moreover, including detailed patient’s history, previous diseases, current diseases, anemia history in family, gynecological history of women were examined. Results: In all two hundred anemic patients, we found one hundred and seventy (85%) patients had deficiency of iron and 30 (15%) patients had inadequacy of non-iron (lack of other minerals) anemia. Most of the patients (58.8%) who had less volume of iron were aged of 21 to 32 Years. On basis of serum ferritin level (SFL), We observed the intensity of deficiency of iron and classify into modest, mildest and acute groups. We found 120 (70.6%) patients had modest IDA (iron deficiency anemia), 20 (11.8%) patients had acute and rest (17.6%) had mildest deficiency of iron anemia. In 160 IDA patient’s women were 95 (55.9%), 40 (23.5%) were men > 19 years and 35 (20.6%) were growing children had an aged < 14 years. Practical implication: This study was conducted to evaluate the frequency of IDA to maintain a better treatment and to reduce the death ratio and to improve quality of life of patients affected by anemia. Conclusion: In this study, we observed deficiency of iron is the most frequent cause in patients of anemia, especially in females. Keywords: blood, Anemia, oxygen, Deficiency of Iron, hemoglobin level,